Study of factors that influence product quality at Hicom Diecastings Sdn Bhd / Muhamad Lokhman Mahmud - Mahmud, Muhamad Lokhman (Faculty of Business and Management, 2010)
The purpose of study is to define study of factors that influence product quality at Hicom Dieastings Sdn Bhd. The collection of information gathered from the secondary data trough the journals local, interview and observation. From the study, researcher identified four major factors arises is people, machine, method and also material and maintenance to implement the superior quality of the products by Hicom Diecastings. Conclusion, researcher gives some suggestion on improvement in their right approach to produce the superior quality parts and implement in the future.